Dental Calculus as The Unique Calcified Oral Ecosystem A Review Article - Natallia Pranata (Denta Journal Kedokteran Gigi, 2019)
The prevalence of periodontal disease in Indonesians is very high, which is around 95%, and 70% of these values occur above 30 years or the adult age group. There is controversy about whether dental calculus is an etiological factor in periodontal disease, or is it just a predisposing factor. Dental Calculus is a calcified oral ecosystem or dental plaque, can accumulate on supragingival or subgingival. Plaque is a bacterial biofilm complex on the tooth surface, including pathogenic microorganisms that invade periodontal tissue. Periodontal disease is the result of interactions between pathogens and the host immune system. Damage to periodontal tissue can occur if the pathogenicity of the microflora is more dominant in the immune response. In calcified conditions, these microorganisms lose their pathogenicity. The dental calculus is one form of the body's defense mechanism against pathogens. But the accumulation of dental calculus, with its rough surface, is a predisposing factor for plaque accumulation. The oral ecosystem trapping on the unique calcified material which are called dental calculus.